2006
DOI: 10.1121/1.2188331
|View full text |Cite
|
Sign up to set email alerts
|

Language redundancy predicts syllabic duration and the spectral characteristics of vocalic syllable nuclei

Abstract: The language redundancy of a syllable, measured by its predictability given its context and inherent frequency, has been shown to have a strong inverse relationship with syllabic duration. This relationship is predicted by the smooth signal redundancy hypothesis, which proposes that robust communication in a noisy environment can be achieved with an inverse relationship between language redundancy and the predictability given acoustic observations (acoustic redundancy). A general version of the hypothesis pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
150
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(172 citation statements)
references
References 24 publications
15
150
7
Order By: Relevance
“…Results of the study showed that vowels were more centralized with increased language redundancy (i.e., higher predictability), vowel quality in prominent syllables was more distinct than in syllables that were not prominent, and spectral characteristics of vowels were also more distinct in syllables before prosodic boundaries than in syllables at word-or at no boundary. Aylett and Turk (2006) concluded that language redundancy and acoustic redundancy show an inverse relationship which is mediated and implemented through prosodic structure.…”
Section: Prosody As An Interface Between Surprisal and The Signalmentioning
confidence: 99%
See 3 more Smart Citations
“…Results of the study showed that vowels were more centralized with increased language redundancy (i.e., higher predictability), vowel quality in prominent syllables was more distinct than in syllables that were not prominent, and spectral characteristics of vowels were also more distinct in syllables before prosodic boundaries than in syllables at word-or at no boundary. Aylett and Turk (2006) concluded that language redundancy and acoustic redundancy show an inverse relationship which is mediated and implemented through prosodic structure.…”
Section: Prosody As An Interface Between Surprisal and The Signalmentioning
confidence: 99%
“…Aylett and Turk (2006) investigated the influence of prosodic structure and predictability on vowel characteristics in General American English read speech. Results of the study showed that vowels were more centralized with increased language redundancy (i.e., higher predictability), vowel quality in prominent syllables was more distinct than in syllables that were not prominent, and spectral characteristics of vowels were also more distinct in syllables before prosodic boundaries than in syllables at word-or at no boundary.…”
Section: Prosody As An Interface Between Surprisal and The Signalmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies (Jurafsky et al 2001, Bell et al 2003, Pluymaekers et al 2005a, Aylett and Turk 2006 have assessed the correlation between a measure of informational redundancy and a measure of phonetic reductionfor example the number of absent segments or syllables relative to the word's canonical realisation -and found it to be significant. These studies have two common features.…”
Section: Introductionmentioning
confidence: 99%